Digital Transformation of Health Quality Services in the Healthcare Industry during Disruption and Society 5.0 Era - Denok Kurniasih; Paulus Israwan Setyoko; Anggara Setya Saputra (IJOSMAS, 2022)
The purpose of this study is to analyze the digital transformation of service quality in the health industry in the era of disruption and society 5.0. This research method is a literature review, which examines digital transformation literacy from articles in reputable international journals.Digital transformation has played a role in revolutionizing various industries, especially in the health sector. Technology in the health sector allows an individual to have a healthier life, a longer life expectancy, and a more productive life. In preparation for the era of disruption 4.0, there are still many hospitals and health care facilities that face various challenges. The main challenges are felt in terms of the ambiguity of laws and regulations and the lack of harmonization of regulations between related ministries. In addition, from internal factors, the lack of openness, motivation, and good knowledge management on the part of hospital management, medical service doctors, and IT teams in the organization also need to be addressed. Various recommendations to related parties have been formulated in the focus group discussion. Recommendations are addressed to the government, especially those authorized to issue regulations and financial support, as well as hospital management to increase implementation commitment, knowledge management of big data analysis and cloud systems, as well as empowering human resources within the organization. These recommendations are expected to be the first step in realizing a digital-based health system that is able to provide quality health services for the people